Desain Prototipe Meja dan Kursi Pantai Portabel dengan Integrasi Pendekatan Ergonomi, Value Engineering dan Kansei Engineering - Nora Yuanita Restantin; Mirwan Ushada; Makhmudun Ainuri (Institute of Research and Community Outreach - Petra Christian University, 2012)
This research highlighted a methodology to design prototype of portable dining table and chairs for the beach by the integration of Ergonomic, Value Engineering and Kansei Engineering. The case study of the research is on Kuwaru Beach. It has its special features compared to other beach that is an open green space which is filled with pine trees shrimp. The location is become a visitors favorite place in enjoying the beauty of sea and the culinary feature. However sand is exposed to sea breeze could contaminate food. While visitors “lesehan seating” position makes visitors easily get exhausted. This gives an altenative that provides dining facilities to support the outdoor atmosphere with the type rather than “lesehan” based on ergonomic approach and Value Engineering. Research using the concept of Kansei Engineering aims to get the design of portable dining table and chairs which comfortable and practical by developing product based on the imagination consumers. Research result indicated the best performance is obtained by the prototype concept I which have a total cost of Rp 500000.00 and a value based visitors 66.20 × 10-5 and restaurant owner 71.19 × 10 -5.